Normal distribution of alkaline phosphatase levels during pregnancy - Nissim Arbib; Kira Nahum Sacks; Lina Salman; Orly Sneh-Arbib; Alexandra Berezowsky; Eyal Krispin; Eran Hadar (IMR Press, 2021)
Background: Previous small-scale studies have reported alkaline phosphatase (ALP) distribution throughout gestation. This retrospective, observational analysis aimed to establish a large-scale, week-specific nomogram of total ALP during pregnancy, and to address physiological parameters that may impact normal ALP secretion throughout pregnancy. Methods: We analyzed ALP levels during pregnancy among 5285 healthy women from various ethnicities, with uncomplicated, term, singleton gestations, who delivered in a single tertiary medical center, from August 2007 to December 2012. Results: We found that normal gestational ALP is significantly elevated during pregnancy compared to a non-pregnant state (132.2 ± 3.0 IU/L vs. 116.7 ± 2.3 IU/L, p < 0.001), and during the third and second trimesters compared to the first trimester (166.4 ± 1.66, 123.7 ± 2.4 and 95.7 ± 1.6 IU/L, respectively; p < 0.001). ALP levels remained unaffected by the modifiers we explored: neonatal sex, neonatal birthweight and maternal age. Conclusion: ALP levels during pregnancy are higher than in the non-pregnant state, gradually increase from the end of the first trimester to term, peaking just prior to delivery. The nomogram presented here can serve as the basis for comparison between a normal population and those with various pregnancy complications, to determine how ALP is associated with adverse pregnancy outcomes.